1995
DOI: 10.1117/12.221362
|View full text |Cite
|
Sign up to set email alerts
|

<title>Stray-light analysis of the SABER telescope</title>

Abstract: The stray light analysis of the sounding of the atmosphere using broadband emission radiometry (SABER) instrument on the thermosphere-ionosphere-mesosphere energetics and dynamics (TIMED) mission is discussed. Relevant mission objectives and operating conditions are stated to define the stray light problem. Since SABER is an earth limb viewing sensor, the telescope must be designed for large off-axis rejection. Described are the key design features which make the instrument well suited for its mission. Represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
5
0
1
Order By: Relevance
“…The stray light analysis program APART was used to predict SABER's off-axis response and to aid in the telescope design 5,6 . The software model showed that mirror scatter is the dominant source of stray light for the short wavelength channels.…”
Section: Comparison Of Measured Results To Software Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The stray light analysis program APART was used to predict SABER's off-axis response and to aid in the telescope design 5,6 . The software model showed that mirror scatter is the dominant source of stray light for the short wavelength channels.…”
Section: Comparison Of Measured Results To Software Modelmentioning
confidence: 99%
“…The instrument description and mission objectives are described in greater detail elsewhere 1,2 . Stray light analyses performed using the software programs APART 3 and ASAP 4 have also been documented [5][6][7] . The results of the off-axis response measurement of SABER are presented in this report.…”
Section: Introductionmentioning
confidence: 99%
“…SABER's optical system was designed specifically to have extremely high rejection of off-axis light. Initial analysis of SABER's stray light performance is reported by Stauder et al (1995). During the development of the instrument, a stray light analysis was performed using a non-sequential ray tracing Zemax model of SABER and an SDL software program to compute the Normalized Detector Irradiance (NDI).…”
Section: Saber Stray Light Parametersmentioning
confidence: 99%
“…系统杂散光抑制水平主要由 PST 进行评价, 其定义为光学系统视场外离轴角 θ 的光源经光学系统后, 在像面 处产生的辐照度 Ed(θ)与垂直于该点源的入瞳处辐照度 Ei(θ)的比值 [19][20] :…”
Section: -unclassified